Atypical polypoid adenomyoma: insights into recurrence, malignant transformation and management: a case report - Mammen, Kitty E.; Sheeba, Asiya; Pillai, Swapna S.; Praseeda, Indira; Thomas, Chandni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Atypical polypoid adenomyoma (APAM) is a rare, benign mixed epithelial-mesenchymal tumor of the uterus. It is characterized by its polypoid growth pattern and atypical histological features. This study aims to consolidate current knowledge regarding its clinical presentation, diagnostic criteria, treatment options, and potential for malignancy. There is a significant rate of recurrence associated with this tumor. It consists of unusual endometrial glands interspersed with bundles of smooth muscle fibers. It is frequently diagnosed in young women and may coexist with or progress to atypical endometrial hyperplasia or endometrioid endometrial carcinoma. We report a case of a 35-year-old woman affected by APAM treated with hysteroscopic resection. Given the risk of recurrence and progression, APAM might be treated via hysterectomy in patients with no desire for pregnancy.